12. Simplify (15x2 – 24x + 9) / (3x – 3) =
A. 5x + 3 C. 5x + 13 with a –30 remainder
B. 5x – 3 D. 5x – 13 with a –30 remainder

(15x2 – 24x + 9) / (3x – 3) = 3(5x^2 - 8x + 3)/3(x - 1) = (5x^2 - 8x + 3)/(x - 1) = (x - 1)(5x - 3)/(x - 1) = 5x - 3

Question

Asked 4/11/2014 3:56:41 PM

Updated 4/12/2014 8:45:41 AM

1 Answer/Comment

Rating

3

(15x2 – 24x + 9) / (3x – 3)

= 3(5x^2 - 8x + 3)/3(x - 1)

= (5x^2 - 8x + 3)/(x - 1)

= (x - 1)(5x - 3)/(x - 1)

= 5x - 3

= 3(5x^2 - 8x + 3)/3(x - 1)

= (5x^2 - 8x + 3)/(x - 1)

= (x - 1)(5x - 3)/(x - 1)

= 5x - 3

Added 4/12/2014 8:45:41 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/12/2014 8:49:35 AM]

20. Find the value or values of y in the quadratic equation y2 + 4y + 4 = 7.
A. y = 2, y = 7 C. y = –2 , y = 2
B. y = 2 + 2 , y = 2 – 2 D. y = –2 + , y = –2 – **Weegy:** 1 (More)

Question

Expert Answered

Updated 4/22/2014 9:37:14 PM

1 Answer/Comment

27,932,666

questions answered

There are no comments.